1998
DOI: 10.1097/00005373-199808000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Severe Hemorrhagic Shock and Resuscitation in Rats Does Not Cause Subtle Brain Damage

Abstract: HS at MAP 40 mm Hg for 60 minutes or MAP 30 mm Hg for 45 minutes does not cause subtle functional or histologic brain damage in surviving rats. Controlling MAP at 30 mm Hg carries a risk of sudden cardiac arrest. These data suggest that limited fluid resuscitation, to maintain MAP at about 40 mm Hg, as recommended for victims of penetrating trauma with uncontrolled HS, is safe for the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 26 publications
3
24
3
Order By: Relevance
“…However, by 21 days, significant CA3 cell death was not evident in either insult. HS alone did not produce appreciable CA1 or CA3 death as assessed by FJC or H&E cell counts, consistent with our prior work (Carrillo et al, 1998;Dennis et al, 2009). Adding an HS insult with a MAP of *35-45 mm Hg for 90 min after CCI exacerbated only CA1 cell death (Dennis et al, 2009).…”
supporting
confidence: 86%
“…However, by 21 days, significant CA3 cell death was not evident in either insult. HS alone did not produce appreciable CA1 or CA3 death as assessed by FJC or H&E cell counts, consistent with our prior work (Carrillo et al, 1998;Dennis et al, 2009). Adding an HS insult with a MAP of *35-45 mm Hg for 90 min after CCI exacerbated only CA1 cell death (Dennis et al, 2009).…”
supporting
confidence: 86%
“…However, it is important to note that all animals were subjected to the same catheterizations. This is in concert with results of another study reporting no persistent limb ischemia or functional deficits after femoral vessel cannulation and ligation in rats assessed with an identical battery of motor tests (Carrillo et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
“…A modified Morris water maze (MWM) task was used to evaluate spatial learning and memory (Morris, 1984;Carrillo et al, 1998). The maze used a 1.8 m diameter and 60 cm high pool filled with non-opaque water (25-27°C) to a depth of 28 cm and a clear Plexiglas stand 10 cm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies from our laboratory showed that with femoral artery cannulation and shock at MAP ϭ 20 to 25 mmHg for 30 min, survival was nearly 100%, even in animals receiving no resuscitation (shocked, nonresuscitated, controls; unpublished data). Lethal rat hemorrhagic models from different investigators have shown that MAP was lower and the shock time was longer using femoral cannulation than with carotid cannulation [2][3][4][5]. In one study, no functional or histological brain damage was noted in rats cannulated through the femoral artery and bled to a MAP of 40 mmHg for 60 min, or a MAP of 30 mmHg for 45 min [5].…”
Section: Discussionmentioning
confidence: 99%